Data from: A worldwide perspective on the population structure and genetic diversity of bottlenose dolphins (Tursiops truncatus) in New Zealand - Tezanos-Pinto, Gabriela; Baker, Charles S; Russell, Kirsty; Martien, Karen; Baird, Robin; Hutt, Alistair; Stone, Gregory; Mignucci-Giannoni, Antonio A; Caballero, Susana; Endo, Tetsuya; Lavery, Shane; Oremus, Marc; et al. (Zenodo, 2009)
Bottlenose dolphins (Tursiops truncatus) occupy a wide range of coastal and pelagic habitats throughout tropical and temperate waters worldwide. In some regions, "inshore" and "offshore" forms or ecotypes differ genetically and morphologically, despite no obvious boundaries to interchange. Around New Zealand, bottlenose dolphins inhabit 3 coastal regions: Northland, Marlborough Sounds, and Fiordland. Previous demographic studies showed no interchange of individuals among these populations. Here, we describe the genetic structure and diversity of these populations using skin samples collected with a remote biopsy dart. Analysis of the molecular variance from mitochondrial DNA (mtDNA) control region sequences (n = 193) showed considerable differentiation among populations (Fst = 0.17, Φst = 0.21, P < 0.001) suggesting little or no female gene flow or interchange. All 3 populations showed higher mtDNA diversity than expected given their small population sizes and isolation. To explain the source of this variation, 22 control region haplotypes from New Zealand were compared with 108 haplotypes worldwide representing 586 individuals from 19 populations and including both inshore and offshore ecotypes as described in the Western North Atlantic. All haplotypes found in the Pacific, regardless of population habitat use (i.e., coastal or pelagic), are more divergent from populations described as inshore ecotype in the Western North Atlantic than from populations described as offshore ecotype. Analysis of gene flow indicated long-distance dispersal among coastal and pelagic populations worldwide (except for those haplotypes described as inshore ecotype in the Western North Atlantic), suggesting that these populations are interconnected on an evolutionary timescale. This finding suggests that habitat specialization has occurred independently in different ocean basins, perhaps with Tursiops aduncus filling the ecological niche of the inshore ecotype in some coastal regions of the Indian and Western Pacific Oceans. ...